2020
DOI: 10.1109/tim.2019.2954235
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Flow Measurement Using Silicone Polymer Wedge Clamp-On Ultrasonic Transducers

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The piezoelectric element in transducer A, shown in green, will be driven to emit a pulse of ultrasound which mode converts to a shear wave in the pipe wall, with the angle of refraction determined by Snell's law. The angle of the transducer wedge is usually chosen such that the angle of incidence is beyond the critical angle for the compression wave [8]. At the pipe wall -fluid boundary, the shear wave is mode converted again into a compression wave in the fluid.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The piezoelectric element in transducer A, shown in green, will be driven to emit a pulse of ultrasound which mode converts to a shear wave in the pipe wall, with the angle of refraction determined by Snell's law. The angle of the transducer wedge is usually chosen such that the angle of incidence is beyond the critical angle for the compression wave [8]. At the pipe wall -fluid boundary, the shear wave is mode converted again into a compression wave in the fluid.…”
Section: Theorymentioning
confidence: 99%
“…1, where the TTD is 20ns. It can be shown that the relationship between the flow velocity, v l , and the TTD, t, is given by [8], [9]…”
Section: Theorymentioning
confidence: 99%